Pengujian Korosi Intergranular Pada Material UNS 06625 Sesuai Standar ASTM G-28 - Ganesha Aryadi; Ari Wibowo; Cahyo Budi Nugroho; Adhe Aryswan (Politeknik Negeri Batam, 2022)
Oil and gas companies are the largest users of steel pipes to produce oil and gas products from the mining, processing and distribution of ready-to-use oil and gas. Steel pipes used in the oil and gas industry can reach tens to thousands of kilometers with many welded joints every few meters. The possibility of corrosion on steel pipes is very large, so a corrosion-resistant coating is needed. Inconel material is often used as a coating material for the inside of steel pipes which is done by cladding welding. In this research, intergranular corrosion testing of the Inconel material layer as a result of cladding welding was carried out on steel pipes with filler metal UNS N06625 to determine the material's susceptibility to corrosion caused by the flow of oil and gas fluid in the pipe. The filler metals used were Ra***tna 625 and Nov***etal 625. Intergranular corrosion testing was carried out using ASTM G-28 standards. The results of the intergranular corrosion test showed that the cladding layer used filler metal for the Ra***tna 625 and Nov***etal 625 brands. No intergranular corrosion was observed, but there was uniform corrosion on the Ra***tna 625 brand with a corrosion rate of 0.46 mm/ year and 0.50 mm/year on the brand Nov***etal 625.